A Model of Creativity for Regional Culinary MSMEs: Developing Innovative Strategies - Yulianty, Puspa Dewi; Aziz, Muhammad Taufik (SENTRALISASI, 2024)
In tight business competition and disruptive environmental conditions, the performance of Culinary MSMEs is the main support for economic growth. This research analyzes the influence of emotional intelligence and cognitive abilities on the creativity and business performance of Culinary MSMEs. This    is quantitative research using the structural equation modeling method with Smart-PLS software. The data in this research is primary data obtained through distributing questionnaires to respondents consisting of 190 Muhammadiyah Culinary MSEs in the Cirebon. The results of the analysis show that intelligence and creativity of employees influence the business performance of Culinary MSMEs, while cognitive ability does not influence the performance of Culinary MSMEs. Furthermore, this research finds that emotional intelligence and cognitive ability influence the creativity of Culinary MSMEs.